Allelopathic hormesis and potent allelochemicals from multipurpose tree Moringa oleifera leaf extract. (2nd January 2021) - Perveen, Shagufta; Mushtaq, Muhammad Naeem; Yousaf, Muhammad; Sarwar, Nighat
Abstract: The secondary metabolites produced by higher plants may act as allelochemicals to stimulate or inhibit growth of other plant species. Moringa oleifera is a multipurpose tree which have been reported, in separate studies, to promote growth of other plant species at low concentrations and inhibit the growth at high concentrations. However, allelopathic hormesis and allelochemicals from Moringa oleifera has not been reported. The present studies were conducted to evaluate hormesis, allelopathic potential and allelochemicals from Moringa oleifera leaf extract using Lepidium sativum as a test species. The results revealed that aqueous leaf extract of Moringa oleifera promoted the shoot growth of Lepidium sativum by 41% at lowest tested concentration of 2.5%, while the highest tested concentration (10%) of leaf extract inhibited shoot length and root length of Lepidium sativum by 38% and 85%, respectively, showing allelopathic hormesis. Twelve allelochemicals (p-coumaric acid, salicylic acid, p-hydroxybenzoic acid, m-coumaric acid, protocatechuic acid, ferulic acid, p-hydroxysalicylic acid, syringic acid, vanillic acid, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde and gallic acid) were identified from leaf extract of Moringa oleifera . The results suggest that Moringa oleifera exhibit allelopathic hormesis which may have critical impact on defence, survival and invasion of plants in natural as well as agroecosystems.